Steller's Eiders Polysticta stelleri wintering in Europe: numbers, distribution and origin - NygÃ¥rd, Torgeir; Frantzen, BjÃ¸rn; Å vaÅ¾as, Saulius (Wildfowl, 1995)
Steller's Eider is among the most northern-living of duck species at all seasons. The recent decline of the species in North America has now increased the awareness of the population wintering in northern Europe. The size of this wintering population is estimated from the available information at 30- 50,000 birds, which suggests that the western population is now of the same magnitude as the eastern one that winters in the Pacific. The most important western wintering area extends from Varangerfjorden in north-eastern Norway to the ice-edge on the Kola coast in north-west Russia. Important winter areas have been found recently on the coasts of Lithuania and Estonia in the eastern Baltic. Recent information about breeding Steller's Eiders on the tundras of Taymyr, Yamal and Gyda peninsulas confirms the existence of a substantial population west of Khatanga, that migrates to the west and winters in North Atlantic and Baltic waters.